2016
DOI: 10.1001/jamacardio.2015.0300
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Risk Prediction Models for Cardiovascular Events in Black Adults

Abstract: IMPORTANCE Cardiovascular risk assessment is a fundamental component of prevention of cardiovascular disease (CVD). However, commonly used prediction models have been formulated in primarily or exclusively white populations. Whether risk assessment in black adults is dissimilar to that in white adults is uncertain. OBJECTIVES To develop and validate risk prediction models for CVD incidence in black adults, incorporating standard risk factors, biomarkers, and subclinical disease. DESIGN, SETTING, AND PARTIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 49 publications
2
45
0
Order By: Relevance
“…First, around 37% of all the JHS participants were excluded from this study mainly because of missing antihypertensive medication variable and missing echo parameters. Antihypertensive medication use is a significant risk factor for cardiovascular events in this population 29. Therefore, we excluded those participants.…”
Section: Discussionmentioning
confidence: 99%
“…First, around 37% of all the JHS participants were excluded from this study mainly because of missing antihypertensive medication variable and missing echo parameters. Antihypertensive medication use is a significant risk factor for cardiovascular events in this population 29. Therefore, we excluded those participants.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the findings in our work provide therapeutic context to recent work from Fox and colleagues in JHS. Fox et al demonstrated good calibration and risk discrimination of CVD risk estimates in African Americans using PCE, not significantly improved with biomarker or ancillary imaging 22 . Several key differences between the work from Fox et al and ours merit mention.…”
Section: Discussionmentioning
confidence: 99%
“…First, we sought to extend prior work in Caucasians 7 by fitting Cox proportional hazards regression models and estimating annualized event rates for incident CVD as a function of statin eligibility by newer ACC/AHA guidelines versus ATP-III. Event rates were calculated per 1000 patient-years of follow-up, analogous to a recently published study 22 . In the subgroup of 1790 individuals with CT imaging, we examined whether the presence of CAC by CT imaging would be associated with CVD risk independent of statin eligibility by newer ACC/AHA guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…A number of other risk prediction models have been developed across a variety of study groups (18,2225). Although the Pooled Cohort risk equations have exhibited good test properties in several studies, the choice of equation to estimate CVD risk in a specific setting relates to validation data showing good discrimination and calibration in the patients of interest (2629). …”
Section: Estimating Cvd Riskmentioning
confidence: 99%